Metastable hybridization-based DNA information storage to allow rapid and permanent erasure - Jangwon Kim (Nature Portfolio, 2020)
The chemical stability of DNA makes complete erasure of DNA-encoded data difficult. Here the authors mix true and false messages, differentiated by whether a truth marker oligo is bound to it, and show that brief exposure to elevated temperatures randomizes the binding of truth markers preventing data recovery.